2003
DOI: 10.1021/ac030135y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Five Tobacco-Specific Nitrosamines in Mainstream Cigarette Smoke by Isotope Dilution Liquid Chromatography/Electrospray Ionization Tandem Mass Spectrometry

Abstract: Tobacco-specific nitrosamines (TSNAs) have been previously implicated as a source of carcinogenicity in tobacco and cigarette smoke. Accurate quantification of these chemicals is needed to help assess public health risk. We have developed and validated a specific and sensitive method to simultaneously measure five TSNAs in the particulate phase of mainstream tobacco smoke. Cigarette smoke particulate, produced using standardized machine smoking protocols, was collected on a Cambridge filter pad. The particulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 19 publications
1
69
0
1
Order By: Relevance
“…In all cases, MDLs and MQLs were significantly below the levels determined in the SHS samples (see below). Furthermore, compared to other methods which involve a preconcentration step and clean-up procedure, MDLs for this method are much lower than for the GC/TEA method, are similar to those found using LC/MS/MS [15][16][17] and are better than those reported by Zhou et al [19] using GC-IT-MS/MS. Lower MDLs may be attained by using an accelerated solvent extraction (ASE) with lower solvent volumes, or employing a preconcentration step using rotary evaporator or solid phase cartridges (SPE).…”
Section: Sensitivitysupporting
confidence: 74%
See 4 more Smart Citations
“…In all cases, MDLs and MQLs were significantly below the levels determined in the SHS samples (see below). Furthermore, compared to other methods which involve a preconcentration step and clean-up procedure, MDLs for this method are much lower than for the GC/TEA method, are similar to those found using LC/MS/MS [15][16][17] and are better than those reported by Zhou et al [19] using GC-IT-MS/MS. Lower MDLs may be attained by using an accelerated solvent extraction (ASE) with lower solvent volumes, or employing a preconcentration step using rotary evaporator or solid phase cartridges (SPE).…”
Section: Sensitivitysupporting
confidence: 74%
“…For example, Caldwell and Conner [26] suggested that artifacts form via nicotine nitrosation during smoke collection. In contrast, other groups [15,27] did not observe artifact formation during collection of TSNAs on untreated Cambridge Filters. It has been reported that the formation of artifactual nitrosamines can be reduced with the addition of ascorbic acid to the sample collection system [26].…”
Section: Artifact Formationmentioning
confidence: 83%
See 3 more Smart Citations